Challenges in Maximising the Value from Epithermal Gold Deposits - S Konopa; R Chesher; E Gleeson; P Allen; D Boakye (The Australasian Institute of Mining and Metallurgy, 2015)
"An EXTENDED ABSTRACT is available for download. A full-length paper was not prepared for this presentation. Not only do epithermal gold deposits provide many challenges in estimating mineral resources, the complexities of these deposits also provide technical challenges in assessing appropriate mining and processing strategies, as well as social and environmental planning and management. The characteristics of epithermal gold deposits include being highly variable with respect to geometry and gold grade distribution, the presence of other economic contributors, mineralogy, texture, rock strength, weathering and alteration overprint. These characteristics influence the economic value of mining projects in an interlinked manner. Consequently, successful exploitation of epithermal deposits requires a holistic approach, coupled with the effective integration of geological data to meet all aspects of mine development decision-making. This paper presents examples of the key technical challenges encountered in estimating and mining epithermal deposits. It also highlights why these issues need to be addressed from the viewpoint of geology, sampling, resource estimation, mine planning, mineral processing and social and environmental planning for the true value of the mining project to be realised.CITATION:Konopa, S, Chesher, R, Gleeson, E, Allen, P and Boakye, D, 2015. Challenges in maximising the value from epithermal gold deposits, in Proceedings PACRIM 2015 Congress, pp 127–132 (The Australasian Institute of Mining and Metallurgy: Melbourne)."